Classification of Enterobacteriaceae by minimization of stochastic complexity - Gyllenberg, H G; Gyllenberg, M; Koski, T; Lund, T; Schindler, J; Verlaan, M (Microbiology (Reading, England), 1997)
A new method for classifying bacteria is presented and applied to a large set of biochemical data for the Enterobacteriaceae. The method minimizes the bits needed to encode the classes and the items or, equivalently, maximizes the information content of the classification. The resulting taxonomy of Enterobacteriaceae corresponds well to the general structure of earlier classifications. Minimization of stochastic complexity can be considered as a useful tool to create bacterial classifications that are optimal from the point of view of information theory.
Keywords: information theory; classification; taxonomy; Enterobacteriaceae; stochastic complexity